A Phase II study of nab-Paclitaxel (nab-P) in patients with advanced non-small cell lung cancer with EGFR mutations after frontline tyrosine kinase inhibitor therapy. (2021) - Baik, Christina; Lee, Sylvia; Cook, Kitty; Wallace, Sarah; Wood, Rebecca; Santana-Davila, Rafael; Chow, Laura; Rodriguez, Cristina; Eaton, Keith D.; Martins, Renato
Highlights: Single agent nab -paclitaxel was associated with modest efficacy in patients with advanced EGFR mutated non-small cell lung cancer. Platinum based chemotherapy remains standard of care in this patient population who are chemotherapy eligible but nab -paclitaxel monotherapy could be an option in patients who are platinum ineligible. CNS progression is a frequent site of disease progression and this underscores the importance of CNS evaluation at progression to tyrosine kinase inhibitor therapy to avoid symptomatic progression in which neurologic deficits are sometimes irreversible. Ongoing trials of chemoimmunotherapy will further clarify the optimal chemotherapy based regimen in this patient population. Abstract: Background: Patients with metastatic non-small cell lung cancer (NSCLC) harboring a sensitizing EGFR mutation have effective targeted therapy options initially but most patients eventually progress and receive cytotoxic chemotherapy. In this single-institution phase II study, we evaluated the role of nab -paclitaxel monotherapy in this patient population. Patients and Methods: Patients with metastatic NSCLC with an activating EGFR mutation whose disease progressed after frontline tyrosine kinase inhibitor therapy and who were chemotherapy naïve received nab -paclitaxel 125 mg/m2 on days 1, 8 and 15 in a 28-day cycle. The primary endpoint was response rate per RECIST 1.1 and secondary endpoints were duration of response, progression free survival, toxicity and overall survival. Results: A total of 27 patients were enrolled and 21 patients were evaluable for response. Median age was 65 (range 52–81), 69% of patients were women, 42% of patients did not having a smoking history. 31% of patients had central nervous system (CNS) metastatic disease at baseline. Confirmed partial response was documented in 9 of 26 patients (35%, 95% CI 17–56) and disease control rate was 58% (95% CI 35–73). CNS was a common first site of progression. Median progression free survival was 4.0 months (95% CI 1.8–5.2). No new safety signals were observed. Conclusion: Single agent nab -paclitaxel showed modest antitumor activity in patients with EGFR mutation positive NSCLC and may be an option in patients who are platinum ineligible. Patients often progressed in the CNS and the results underscores the importance of CNS activity of systemic therapies in this patient population.